Prostatic urethral lift for the treatment of lower urinary tract symptoms in men with benign prostatic hyperplasia - Jung, Jae Hung (Cochrane Database Syst Rev, 2019)
BACKGROUND: A variety of minimally invasive surgical approaches are available as an alternative to transurethral resection of prostate (TURP) for the management of lower urinary tract symptoms (LUTS) in men with benign prostatic hyperplasia (BPH). A recent addition to these is prostatic urethral lift (PUL). OBJECTIVES: To assess the effects of PUL for the treatment of LUTS in men with BPH. SEARCH METHODS: We performed a comprehensive search of multiple databases (the Cochrane Library, MEDLINE, Embase, LILACS, Scopus, Web of Science, and Google Scholar), trials registries, other sources of grey literature, and conference proceedings with no restrictions on the language of publication or publication status up until 31 January 2019. SELECTION CRITERIA: We included parallel group randomized controlled trials (RCTs). While we planned to include non‐RCTs if RCTs had provided low‐certainty evidence for a given outcome and comparison, we could not find any non‐RCTs. DATA COLLECTION AND ANALYSIS: Two review authors independently screened the literature, extracted data, and assessed risk of bias. We performed statistical analyses using a random‐effects model and interpreted them according to the Cochrane Handbook for Systematic Reviews of Interventions. We planned subgroup analyses by age, prostate volume, and severity of baseline symptoms. We used the GRADE approach to rate the certainty of the evidence. MAIN RESULTS: We included two RCTs with 297 participants comparing PUL to sham surgery or TURP. The mean age was 65.6 years and mean International Prostate Symptom Score was 22.7. Mean prostate volume was 42.2 mL. We considered review outcomes measured up to and including 12 months after randomization as short‐term and later than 12 months as long‐term. For patient‐reported outcomes, lower scores indicate more urological symptom improvement and higher quality of life. In contrast, higher scores refers to better erectile and ejaculatory function. PUL versus sham: based on one study of 206 randomized participants with short follow‐up (up to three months), PUL may lead to a clinically important improvement in urological symptom scores (mean difference (MD) –5.20, 95% confidence interval (CI) –7.44 to –2.96; low‐certainty evidence) and likely improves quality of life (MD –1.20, 95% CI –1.67 to –0.73; moderate‐certainty evidence). We are uncertain whether PUL increases major adverse events (very low‐certainty evidence). There were no retreatments reported in either study group by three months. PUL likely results in little to no difference in erectile function (MD –1.40, 95% CI –3.24 to 0.44; moderate‐certainty evidence) and ejaculatory function (MD 0.50, 95% CI –0.38 to 1.38; moderate‐certainty evidence). PUL versus TURP: based on one study of 91 randomized participants with a short follow‐up (up to 12 months), PUL may result in a substantially lesser improvement in urological symptom scores than TURP (MD 4.50, 95% CI 1.10 to 7.90; low‐certainty evidence). PUL may result in a slightly reduced or similar quality of life (MD 0.30, 95% CI –0.49 to 1.09; low‐certainty evidence). We are very uncertain whether PUL may cause fewer major adverse events but increased retreatments (both very low‐certainty evidence). PUL probably results in little to no difference in erectile function (MD 0.80, 95% CI –1.50 to 3.10; moderate‐certainty evidence), but probably results in substantially better ejaculatory function (MD 5.00, 95% CI 3.08 to 6.92; moderate‐certainty evidence). With regards to longer term follow‐up (up to 24 months) based on one study of 91 randomized participants, PUL may result in a substantially lesser improvement in urological symptom score (MD 6.10, 95% CI 2.16 to 10.04; low‐certainty evidence) and result in little worse to no difference in quality of life (MD 0.80, 95% CI 0.00 to 1.60; low‐certainty evidence). The study did not report on major adverse events. We are very uncertain whether PUL increases retreatment (very low‐certainty evidence). PUL likely results in little to no difference in erectile function (MD 1.60, 95% CI –0.80 to 4.00; moderate‐certainty evidence), but may result in substantially better ejaculatory function (MD 4.30, 95% CI 2.17 to 6.43; low‐certainty evidence). We were unable to perform any of the predefined secondary analyses for either comparison. We found no evidence for other comparisons such as PUL versus laser ablation or enucleation. AUTHORS' CONCLUSIONS: PUL appears less effective than TURP in improving urological symptoms both short‐term and long term, while quality of life outcomes may be similar. The effect on erectile function appears similar but ejaculatory function may be better. We are uncertain about major adverse events short‐term and found no long‐term information. We are very uncertain about retreatment rates both short‐term and long‐term. We were unable to assess the effects of PUL in subgroups based on age, prostate size, or symptom severity and also could not assess how PUL compared to other surgical management approaches. Given the large numbers of alternative treatment modalities to treat men with LUTS secondary to BPH, this represents important information that should be shared with men considering surgical treatment.